Computer aided verification. 27th International Conference, CAV 2015, San Francisco, CA, USA, July 18-24, 2015, Proceedings /: 27th International Conference, CAV 2015, San Francisco, CA, USA, July 18-24, 2015, Proceedings. Part II : (2015) - Unknown
No abstract available